OPTIMATION OF COMPOSTION OF SPAN 80-CRODURET 50-PROPYLENE GLYCOL AS EMULSIFIER OF STRAWBERRY JUICE (Fragaria vesca L.) EMULGEL AND TRANSPORT TEST THROUGH SHED SNAKE SKIN MEMBRANE - ERMAWATI, DIAN EKA (Journal of Food and Pharmaceutical Sciences, 2016)
Strawberry (Fragaria vesca L.) contains many nutrients that are beneficial to health because rich of antioxidant such as ascorbic acid, quercetin-3-β-D–glucoside, anthocyanin pelargonidin-3-O-glucoside and cyanidin-3-glucoside. Amount of anthocyanins and flavonoids in strawberry during process will decline respectively 53% for pelargonidin-3-O-glucoside and 40% for flavonoid quercetin. Using water-oil emulsion (w/o) topically less convenient, so it needs to be dispersed in the matrix gel to help sustain the permeation of the active components of strawberry juice into the stratum corneum. Emulsion consisting of water and oil components are not mixed with each other, thus requiring additional emulsifier to create a system that is homogeneous and stable.The proportion of combination of emulsifier as span 80, croduret 50, propylene glycol are optimized, to produce an optimum formula with good physical stability. The optimization method was Simplex Lattice Design by using Design Expert® software 7.1.5. The results of the response of the assessed physical parameter were viscosity, separation ratio (F), and diameter of emulsion globule. The optimum formula have measured physical stability test, active ingredient of flavonoid and anthocyanins, which  then was conducted  transport  test  through the membrane of shed snake skin by Franz’s model diffusion cells with the flavonoid concentration parameters that were able to pass through the membrane.Emulsion w/o that use combination of 2,00% Span 80; 4,00% croduret 50, and 2,00% of propylene glycol which produce a physically stable emulsion base on Simplex Lattice Design [p-value> 0.05]. Strawberry juice contains 23,3 % of flavonoid, 13,23% of anthocyanin, and IC50 331 µg/mL. The optimum formula of emulgel contains 20% of flavonoids and 11.67% of anthocyanin. The cumulative amount of flavonoid which was transported through the shed snake skin membrane was 117,14 µg/cm2  during five hours. The permeability of membrane shed snake skins is 2,84x10-5 µg/cm2and flux value is 6,6x10-5 µg/secon. Keywords : strawberry juice, emulsifier, Simplex Lattice Design, emulgel, flavonoid